Involvement of Dietary Bioactive Proteins and Peptides in Autism Spectrum Disorders - Siniscalco, Dario; Antonucci, Nicola (Current Protein and Peptide Science, 2013)
Autism and autism spectrum disorders (ASDs) are heterogeneous, severe neurodevelopmental pathologies. These enigmatic conditions have their origins in the interaction of multiple genes and environmental factors. Dysfunctions in social interactions and communication skills, restricted interests, repetitive and stereotypic verbal and non-verbal behaviours are the main core symptoms. Several biochemical processes are associated with ASDs: oxidative stress; endoplasmic reticulum stress; decreased methylation capacity; limited production of glutathione; mitochondrial dysfunction; intestinal impaired permeability and dysbiosis; increased toxic metal burden; immune dysregulation. Current available treatments for ASDs can be divided into behavioural, nutritional and medical approaches, although no defined standard approach exists. Dietary bioactive proteins and peptides show potential for application as health-promoting agents. Nowadays, increasing studies highlight a key role of bioactive proteins and peptides in ASDs. This review will focus on the state-of-the-art regarding the involvement of dietary bioactive proteins and peptides in ASDs. Identification of novel therapeutic targets for ASD management will be also discussed.
Keywords: dietary proteins